THE CONTEMPORARY INTERPRETATION OF GOVERNANCE, SPIRITUAL LEADERSHIP AND SOCIAL RESPONSIBILITY IN THE LEGACY OF MUSOKHON DAHBIDIY (Scientific journal of the Fergana State University, 2026)
This article examines the principles of governance, spiritual leadership, and social responsibility reflected in the legacy of Musokhon Dahbidiy. His ethical and normative views are compared with modern governance models, highlighting their relevance to contemporary democratic reforms, justice, social stability, and leadership culture. The study demonstrates that Dahbidiy’s ideas can contribute to strengthening human dignity, responsible leadership, and social obligation in modern public administration.